Nanomaterials Exhibiting Enzyme-Like Properties (Nanozymes): Current Advances and Future Perspectives - Singh, Sanjay (Frontiers in Chemistry, 2019)
Biological enzymes are macromolecular catalysts that catalyze the biochemical reactions of the natural systems. Although each enzyme performs a particular function, however, holds several drawbacks, which limits its utilization in broad-spectrum applications. Natural enzymes require strict physiological conditions for performing catalytic functions. Their limited stability in harsh environmental conditions, the high cost of synthesis, isolation, and purification are some of the significant drawbacks. Therefore, as an alternative to natural enzymes, recently several strategies have been developed including the synthesis of molecules, complexes, and nanoparticles mimicking their intrinsic catalytic properties. Nanoparticles exhibiting the properties of an enzyme are termed as ‘nanozymes.’ Nanozymes offer several advantages over natural enzymes, therefore, a rapid expansion of the development of artificial biocatalysts. These advantages include simple methods of synthesis, low cost, high stability, robust catalytic performance, and smooth surface modification of nanomaterials. In this context, nanozymes are tremendously being explored to establish a wide range of applications in biosensing, immunoassays, disease diagnosis and therapy, theranostics, cell/tissue growth, protection from oxidative stress, and removal of pollutants. Considering the importance of nanozymes this article has been designed to comprehensively discuss the different enzyme-like properties, such as peroxidase, catalase, superoxide dismutase and, oxidase, exhibited by various nanoparticles.